Computer analysis of images and patterns 14th international conference, CAIP 2011, Seville, Spain, August 29-31, 2011, proceedings, part I - Real, Pedro; Diaz-Pernil, Daniel; Molina-Abril, Helena; Berciano, Ainhoa; Kropatsch, Walter (Lecture notes in computer science, 2011)
TThe two volume set LNCS 6854/6855 constitutes the refereed proceedings of the International Conference on Computer Analysis of Images and Patterns, CAIP 2011, which took place in Seville, Spain, August 29-31, 2011. The 138 papers presented together with 2 invited talks were carefully reviewed and selected from 286 submissions. The papers are organized in topical section on: motion analysis, image and shape models, segmentation and grouping, shape recovery, kernel methods, medical imaging, structural pattern recognition, Biometrics, image and video processing, calibration; and tracking and stereo vision.